Capacity and Performance Enhancement using Massive MIMO Systems for Future Wireless Applications: A Review, Challenges and Research Opportunities - Rajpreet Singh, Paras Chawla (International Journal of Advanced Science and Technology, 2020)
Massive MIMO Systems and use of millimetre Wave Spectrum are seen as fundamental technologies to meet continuously increasing demand of data traffic in near future with seamless connectivity and service quality. This paper provides comprehensive review ofrelated fundamental technology key points, associated challenges and research opportunities to meet the foreseeable growth in data traffic in near future.The usemillimetre Wave Spectrum will provide the availability of relatively large bandwidth, currently the use of millimetre waves is at an evolutionary stage. In this paper the challenges related to harsh channel conditions and possible solutions are presented. Further an important research area and related challenges to fully utilize the available capacity of millimetre Waves is presented.Massive-MIMO has been identified as one of the most prevalent technology for millimetre Wave Communication. It is capable of providing significant improvements in Spectral Efficiency, Energy Efficiency and Hardware Efficiency. Further, the upcoming applications of massive MIMO systems future generation wireless systems are highlighted.